The Entrepreneurial Potential among Undergraduate Students - Megawati Simanjuntak; Irma Awwaliyah; Hayati Hayati; Rico J. Artanto (Fakultas Ekonomi dan Bisnis Universitas Padjadjaran, 2016)
Entrepreneurship plays a vital role in the economic development of any country and it can be linked to economic growth of any nations. The research aimed to identify formal education’s role and self-concept among undergraduate students and its influence towards their entrepreneurial potential. In accomplish the purpose, an online questionnaire was administered to 456 students of Bogor Agricultural University, Indonesia. The collected data was analyzed by multiple regression model. The results revealed that self-concept was positively influence the entrepreneurial potential. The universities can strengthen student self-concept by instilling the values of entrepreneurship and training to shape a good self-concept.